Deepening group psychotherapy with men : stories and insights for the journey - Rabinowitz, Fredric Eldon, 1956- (American Psychological Association, 2019)
This book offers a conceptual framework for working with menƯ--the Deepening framework--along with practical guidance for conducting group therapy with men. In Deepening group psychotherapy, men discover their hopes, fears, losses, frustrations, and traumas, aided by a clinician who uses attentiveness to language and the therapeutic relationship to engage and intervene. Traditional therapy, with its emphasis on vulnerable face-to-face sharing, presents challenges for men socialized to keep their emotional lives private. This book helps clinicians find ways to break down the barriers that keep many men from seeking help, and shows them how to explore men's inner psychological workings. Through detailed therapy dialogues that illustrate moment-to-moment and session-to-session interventions, readers will learn how to connect with men in group settings around issues such as relationships, fear of being dependent on others, grief and loss, sexual identity, pain, illness, and addiction.